Cetuximab-Based Immunotherapy and Radioimmunotherapy of Head-Neck Squamous Cell Carcinoma - Niu, Gang (2010)
PURPOSE: To demonstrate the relationship between antibody delivery and therapeutic efficacy in head and neck cancers, in this study we evaluated the pharmacokinetics and pharmacodynamics of EGFR targeted immunotherapy and radioimmunotherapy by quantitative positron emission tomography (PET) imaging. EXPERIMENTAL DESIGN: EGFR expression on UM-SCC-22B and SCC1 human head and neck squamous cell cancer (HNSCC) cells were determined by flow cytometry and immunostaining. Tumor delivery and distribution of cetuximab in tumor-bearing nude mice were evaluated with small animal PET using (64)Cu-DOTA-cetuximab. The in vitro toxicity of cetuximab to HNSCC cells was evaluated by MTT assay. The tumor-bearing mice were then treated with 4 doses of cetuximab at 10 mg/kg per dose and tumor growth was evaluated by caliper measurement. FDG PET was performed after the third dose of antibody administration to evaluate tumor response. Apoptosis and tumor cell proliferation after cetuximab treatment were analyzed by TUNEL and Ki-67 staining. Radioimmunotherapy was performed with (90)Y-DOTA-cetuximab. RESULTS: EGFR expression on UM-SCC-22B cells is lower than that on SCC1 cells. However, the UM-SCC-22B tumors showed much higher (64)Cu-DOTA-cetuximab accumulation than the SCC1 tumors. Cetuximab induced apoptosis in SCC1 tumors and tumor growth was significantly inhibited, while an agonistic effect of cetuximab on UM-SCC-22B tumor growth was observed. After cetuximab treatment, the SCC1 tumors showed decreased FDG uptake, and the UM-SCC-22B tumors had increased FDG uptake. UM-SCC-22B tumors are more responsive to (90)Y-DOTA-cetuximab treatment than SCC1 tumors, partially due to the high tumor accumulation of the injected antibody. CONCLUSION: Cetuximab has an agonistic effect on the growth of UM-SCC-22B tumors, indicating tumor response to cetuximab treatment is not necessarily related to EGFR expression and antibody delivery efficiency, as determined by PET imaging. Although PET imaging with antibodies as tracers has limited function in patient screening, it can provide guidance for targeted therapy using antibodies as delivery vehicles.